Tracking control of ships based on ADRC−MFAC - Shijie LI; Chengqi XU; Jialun LIU; Ziqian XU; Fanbin MENG (Zhongguo Jianchuan Yanjiu, 2024)
ObjectiveThis paper aims to investigate the complex influence of environmental disturbances on unmanned surface vehicles (USVs) under real ocean conditions, and control USVs to overcome disturbances and realize path following. MethodsAn improved active disturbance rejection controller (ADRC) based on the model-free adaptive control (MFAC) law (ADRC−MFAC) is proposed to establish the non-linear relationship between the input data (rudder angle) and output data (heading angle, angular velocity), and identify the unknown disturbances of the system. In this way, stable heading control can be achieved. Combined with the adaptive line-of-sight (LOS) guidance law, it achieves accurate tracking control through dynamic heading control.ResultsThe simulation results show that the controller can control USVs to approach the preset path quickly and achieve a desirable tracking control effect under complex disturbances. ConclusionThe research results do not depend on the specific model of USV and can provide valuable references for ship tracking control.